2015
DOI: 10.3109/0886022x.2015.1067129
|View full text |Cite
|
Sign up to set email alerts
|

The amino acid mutations of the podocin in proteinuria: a meta-analysis

Abstract: (2015) The amino acid mutations of the podocin in proteinuria: a meta-analysis, Renal Failure, 37:8, 1329-1337 AbstractWhile many previous studies have reported an association between the single-nucleotide polymorphisms (SNPs) of the podocin and proteinuria occurred, a conclusive relationship has not been defined in every oligoallelic state of amino acid (AA) mutations in podocin. In this study, we performed a meta-analysis of the published data to investigate the impact of the oligoallelic AA mutations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…There is a contradiction in literature regarding this variant. While older studies showed this variant as being pathogenic (17,18) the new ones accept it as being benign (19)(20)(21)(22)(23). Despite the fact that there are several studies predicting c.59C>T to have a disease-causing effect in European, North American, Caucasian and South American populations (24), in our study, it was decided to classify it as VUS while further segregation and detailed pedigree analyses were planned.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There is a contradiction in literature regarding this variant. While older studies showed this variant as being pathogenic (17,18) the new ones accept it as being benign (19)(20)(21)(22)(23). Despite the fact that there are several studies predicting c.59C>T to have a disease-causing effect in European, North American, Caucasian and South American populations (24), in our study, it was decided to classify it as VUS while further segregation and detailed pedigree analyses were planned.…”
Section: Discussionmentioning
confidence: 95%
“…Leu169Pro (21), Val180Met (25), Val290Met (21) and Arg-229Gln (21) were classifi ed as VUS because of insuffi cient evidences and lack of segregation analysis. Nevertheless, they are thought to be the cause of clinical manifestation in patients.…”
Section: Discussionmentioning
confidence: 99%